Defect-rich sodium citrate modified carbon-based composite catalyst as well as preparation method and application thereof

By adding sodium citrate to the preparation of layered bimetallic hydroxide/biochar composite catalyst, defect-rich sodium citrate modified carbon-based composite catalyst was prepared, and the existing existing catalysts were solved during the preparation process. Aggregation and metal leaching problems have achieved efficient degradation of neonicotinoid pesticides.

CN119386931APending Publication Date: 2025-02-07NORTHEAST AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411530298.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing layered bimetallic hydroxide/biochar composite catalysts have problems such as aggregation and metal leaching during the preparation process, resulting in active site coverage and secondary contamination, making it difficult to achieve efficient degradation of neonicotinoid pesticides. .

Method used

The defect-rich sodium citrate modified carbon-based composite catalyst is prepared by adding sodium citrate to the preparation of the layered bimetallic hydroxide/biochar composite catalyst to enhance the structural stability and catalytic activity of the catalyst.

Benefits of technology

When the catalyst activates persulfate, it accelerates the decomposition reaction of persulfate, significantly improves the degradation efficiency of neonicotinoid pesticides, and has strong structural stability and catalytic activity, making it suitable for wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386931A_ABST
    Figure CN119386931A_ABST
Patent Text Reader

Abstract

The invention discloses a defect-rich sodium citrate modified carbon-based composite catalyst as well as a preparation method and application thereof, and belongs to the technical field of sewage treatment. The preparation method comprises the following steps: jointly dispersing biochar, soluble ferrous salt, soluble cobalt salt and sodium citrate in water, then adding a mixed solution of sodium hydroxide and sodium bicarbonate, adjusting the pH value of a reaction system to 10-10.5, fully mixing the reaction raw materials, and then carrying out aging reaction, thereby obtaining the biochar-cobalt composite material. The sodium citrate modified carbon-based composite catalyst rich in defects is obtained. The prepared sodium citrate modified carbon-based composite catalyst rich in defects is low in price, stable in structure and high in catalytic activity. When the catalyst is used for activating persulfate, the decomposition reaction of the persulfate can be accelerated. When a catalytic oxidation system formed by the catalyst and persulfate is used for degrading neonicotinoid insecticides in water, the degradation efficiency is high. Meanwhile, the preparation method provided by the invention is simple in process, free of secondary pollution and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sewage treatment, and specifically relates to a defect-rich sodium citrate modified carbon-based composite catalyst, a preparation method and an application thereof. Background Art

[0002] Neonicotinoid insecticides are synthetic nicotine derivatives that are highly active, have a broad spectrum of insecticides, and are low in toxicity to mammals. However, due to their small molecular size, high water solubility, and long half-life, these insecticides are easily adsorbed by the soil, making it easy for pesticide molecules to enter groundwater and surface water and remain in aquatic ecosystems for a long time. Imidacloprid (IMI), as the first generation of neonicotinoid insecticides, is widely used in plant disease and insect pest control. Its mode of action is to target the nicotine acetylcholine receptors in the insect nervous system, causing pest excitement and paralysis, and ultimately leading to their death. However, IMI is a nitrogen-containing heterocyclic compound that is difficult to biodegrade, and traditional sewage treatment processes are also difficult to effectively remove.

[0003] Compared with traditional oxidation technology to activate H 2 O 2 Compared with the generation of ·OH, the persulfate advanced oxidation process destroys the peroxide bond (OO) of persulfate through an activation strategy, generating a large amount of highly oxidizing SO 4 ·- , OH, O 2·- and non-free radicals 1 O 2 , achieving efficient degradation of pollutants. In addition, the persulfate advanced oxidation process has high reaction stability, low pH value requirements, and strong environmental adaptability.

[0004] In recent years, researchers have begun to study the activation of peroxymonosulfate for wastewater treatment using layered double hydroxide / biochar composite catalysts. The catalyst mainly includes directly blending biochar and layered double hydroxide (LDH) and preparing them after drying. However, the existing preparation methods of layered double hydroxide / biochar composite catalysts have serious problems such as aggregation and metal leaching, which lead to active site coverage and secondary pollution. Therefore, providing a biochar-based catalyst with a stable structure and strong catalytic activity is of great significance for activating peroxymonosulfate and achieving efficient degradation of neonicotinoid pesticides, as well as effectively alleviating the environmental pollution caused by neonicotinoid pesticides. Summary of the invention

[0005] To solve the above problems, the present invention provides a defect-rich sodium citrate modified carbon-based composite catalyst and its preparation method and application. By adding sodium citrate in the process of preparing a layered double metal hydroxide / biochar composite catalyst, a carbon-based composite catalyst with stable structure and strong catalytic activity is obtained.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention is to provide a method for preparing a defect-rich sodium citrate modified carbon-based composite catalyst, comprising the following steps:

[0008] Biochar, soluble ferrous salt, soluble cobalt salt and sodium citrate are dispersed together in water, and then a mixed solution of sodium hydroxide and sodium bicarbonate is added to adjust the pH value of the reaction system to 10-10.5. After the reaction raw materials are fully mixed, an aging reaction is carried out to obtain a defect-rich sodium citrate modified carbon-based composite catalyst.

[0009] The addition of sodium citrate in the present invention enhances the synergistic effect of the layered double metal hydroxide and biochar. On the one hand, sodium citrate modification can enhance the structural stability of the modified carbon-based composite catalyst. This stability not only helps to maintain the integrity of the catalyst during the reaction, but also improves the recycling efficiency of Fe2+ / Fe3+ and Co2+ / Co3+ in the reaction system; on the other hand, the structure can provide a large number of defect sites, which can serve as reaction active centers to promote the adsorption and activation of reactants, accelerate the decomposition reaction of persulfate, and significantly enhance the reactivity of the catalyst, thereby improving the degradation efficiency.

[0010] The main function of the sodium hydroxide and sodium bicarbonate used in the present invention is to adjust the pH value of the reaction system. Sodium bicarbonate also plays a buffering role in the system, helping to stabilize the pH value within a narrow range, which is necessary for the stable progress of the reaction and the structural stability of the catalyst.

[0011] In the preparation process of the present invention, the pH value should be controlled at 10 to 10.5. If the pH value exceeds 10.5, it may cause excessive hydrolysis of metal ions such as iron and cobalt in the reaction system, forming uncontrollable precipitation. This precipitate is usually loose in structure, which is not conducive to the formation of the desired layered structure, thereby affecting the structural stability and catalytic efficiency of the catalyst. Too high a pH value may also affect the stability of sodium citrate and its effect as a ligand, thereby weakening its role in regulating the electronic structure of metal ions and improving the availability of active sites. If the pH value is lower than 10, it may not be enough to completely precipitate all metal ions, resulting in insufficient content of active metals in the catalyst, which will directly affect the activity and efficiency of the catalyst. Too low a pH value may also lead to insufficient binding of metal ions to biochar, affecting the overall structure and stability of the catalyst.

[0012] The present invention adopts a chemical precipitation method to in-situ prepare a catalyst composite of layered double metal hydroxide and biochar, thereby avoiding the problem of high energy consumption in the traditional hydrothermal preparation method.

[0013] Preferably, in the reaction system, the concentration of biochar is 10-50 g / L, Fe 2+ The concentration of Co is 0.05mol / L~0.15mol / L, 2+ The concentration of the sodium hydroxide is 0.05mol / L-0.15mol / L, the concentration of the sodium citrate is 0.001-0.01mol / L, the concentration of the sodium hydroxide in the mixed solution of sodium hydroxide and sodium bicarbonate is 0.2-0.4mol / L, and the concentration of the sodium bicarbonate is 0.2-0.4mol / L.

[0014] The present invention can further increase the catalytic active sites of the prepared defect-rich sodium citrate modified carbon-based composite catalyst by adjusting the concentration of each raw material.

[0015] Preferably, the aging reaction is carried out at a temperature of 60 to 80° C. and for a time of 18 to 30 hours.

[0016] The biochar used in the present invention can be prepared by calcining agricultural waste in an inert atmosphere, the agricultural waste includes but is not limited to biomass raw materials such as grapefruit peel, walnut shell and white melon seed peel, the calcination temperature is 500-900°C, the holding time is 1-3h, and the heating rate is 5-10°C / min, and biochar with excellent performance can be obtained. The present invention can provide a possible way for the resource utilization of agricultural waste, which is in line with the concept of "using waste to treat waste".

[0017] The cations of the soluble ferrous salt and the soluble cobalt salt in the present invention are Fe 2+ Source and Co 2+ The anion is inserted in the middle of the LDH structure to balance the charge. Exemplarily, the soluble ferrous salt includes but is not limited to FeCl 2 、Fe(NO 3 ) 2 and FeSO 4 At least one of; the soluble cobalt salt includes but is not limited to CoCl 2 、Co(NO 3 ) 2 and Co(CH 3 COO 2 At least one of .

[0018] Preferably, the aging reaction further includes filtering and drying steps.

[0019] More preferably, the drying temperature is 80-100°C.

[0020] The second technical solution of the present invention is to provide a defect-rich sodium citrate modified carbon-based composite catalyst prepared according to the preparation method of the defect-rich sodium citrate modified carbon-based composite catalyst.

[0021] The third technical solution of the present invention is to provide an application of the above-mentioned sodium citrate modified carbon-based composite catalyst in activating persulfate.

[0022] Technical solution four of the present invention: provides an application of the above-mentioned sodium citrate modified carbon-based composite catalyst in the degradation of neonicotinoid pesticides in water.

[0023] Preferably, the degradation step comprises: adding the sodium citrate-modified carbon-based composite catalyst and persulfate to water containing the neonicotinoid insecticide, and the degradation treatment of the neonicotinoid insecticide in the water is completed after the reaction.

[0024] More preferably, the addition amount of the sodium citrate modified carbon-based composite catalyst is 0.2-0.5 g / L; the addition amount of the persulfate is 0.12-0.48 g / L; the reaction time is 10-30 min; and the concentration of the neonicotinoid insecticide is 1-20 mg / L.

[0025] Exemplarily, the persulfate is peroxymonosulfate (PMS), peroxydisulfate (PDS) or a mixture of both, and in the embodiment of the present invention, it is potassium hydrogen persulfate.

[0026] The beneficial technical effects of the present invention are as follows:

[0027] The defect-rich sodium citrate modified carbon-based composite catalyst prepared by the present invention is low in price, stable in structure and strong in catalytic activity. The catalyst is used to activate persulfate to accelerate the decomposition reaction of persulfate. When the catalytic oxidation system composed of the catalyst and persulfate is used to degrade neonicotinoid pesticides in water, the degradation efficiency is high.

[0028] The iron-cobalt layered double metal hydroxide in the defect-rich sodium citrate modified carbon-based composite catalyst prepared by the present invention can effectively adhere to and disperse on the surface of biochar, effectively solving the problem of monomers being easily agglomerated and inactivated. It is applied in actual sewage treatment and has good degradation ability for neonicotinoid pesticides. At the same time, the preparation method provided by the present invention has a simple process, no secondary pollution, and is suitable for large-scale production.

[0029] The present invention not only provides a new type of catalyst for the efficient degradation of neonicotinoid pesticides in water, but also provides a sodium citrate-modified carbon-based composite catalyst with stable structure and excellent performance, providing new ideas for the design and controllable preparation of carbon-based composite catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The scanning electron microscope image and transmission electron microscope image of the SFCBC prepared in Example 1, wherein (a) is a scanning electron microscope image and (b) is a transmission electron microscope image.

[0031] Figure 2 FTIR comparison chart of raw material biochar, SFCBC prepared in Example 1 and FCBC prepared in Comparative Example 1.

[0032] Figure 3 It is a Raman comparison chart of the raw material biochar, the SFCBC prepared in Example 1, and the FCBC prepared in Comparative Example 1.

[0033] Figure 4 The degradation rate of imidacloprid in water by using different amounts of SFCBC to activate potassium persulfate in Example 3.

[0034] Figure 5 The degradation rate of imidacloprid in water by SFCBC activated with different concentrations of potassium persulfate in Example 4.

[0035] Figure 6 The degradation rate of imidacloprid in water with different pH values ​​by SFCBC activated potassium persulfate in Example 5.

[0036] Figure 7 The degradation rate of different neonicotinoid pesticides in water by SFCBC-activated potassium persulfate in Example 7.

[0037] Figure 8 This is a cycle experiment of SFCBC activating potassium persulfate to degrade imidacloprid in water in Example 8. DETAILED DESCRIPTION

[0038] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0039] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0040] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0042] The steps for preparing the biochar used in the examples and comparative examples of the present invention are as follows:

[0043] 40g of grapefruit peel raw material was washed, dried, crushed and sieved, and heated to 900°C at a heating rate of 10°C / min in a nitrogen atmosphere, kept warm for 2h, and subjected to high-temperature pyrolysis. After cooling, ultrasonic cleaning and drying were performed to obtain biochar, which was recorded as BC. It should be noted that other types of biochar can also achieve the technical purpose of the present invention.

[0044] Example 1

[0045] Preparation of defect-rich sodium citrate-modified carbon-based composite catalysts:

[0046] Take 1g of biochar and disperse it in 100mL of ultrapure water. Then add 0.01mol of ferrous nitrate, 0.01mol of cobalt nitrate hexahydrate and 0.12mmol of sodium citrate. After stirring for 2h, add a mixed solution of 0.4mol / L of sodium hydroxide and 0.4mol / L of sodium bicarbonate dropwise, adjust the pH value to 10, stir for 1h, put it in a 70℃ oven for aging for 24h, then filter it and move it into an oven to dry at 80℃ to obtain a defect-rich sodium citrate modified carbon-based composite catalyst, recorded as SFCBC.

[0047] The SEM and TEM images of the SFCBC prepared in Example 1 are shown in Figure 1 , where (a) is a scanning electron microscope image and (b) is a transmission electron microscope image.

[0048] from Figure 1 It can be seen that the surface of the SFCBC prepared by the present invention contains a large number of fine particles, and the introduction of biochar does not destroy the layered structure of the layered double metal hydroxide.

[0049] Comparative Example 1

[0050] Preparation of carbon-based composite catalysts:

[0051] Take 1g of biochar and disperse it in 100mL of ultrapure water. Then add 0.01mol of ferrous nitrate and 0.01mol of cobalt nitrate hexahydrate. After stirring for 2h, add a mixed solution of 0.4mol / L of sodium hydroxide and 0.4mol / L of sodium bicarbonate dropwise, adjust the pH value to 10, stir for 1h, put it in a 70℃ oven for aging for 24h, then filter it and move it into an oven to dry at 80℃ to obtain a carbon-based composite catalyst, recorded as FCBC.

[0052] Comparative Example 2

[0053] Preparation of carbon-based composite catalysts:

[0054] Take 1g of biochar and disperse it in 100mL of ultrapure water. Then add 0.01mol of cobalt nitrate hexahydrate and stir for 2h. Then add a mixed solution of 0.4mol / L of sodium hydroxide and 0.4mol / L of sodium bicarbonate dropwise. Adjust the pH value to 10. After stirring for 1h, put it in a 70℃ oven for aging for 24h. Then filter it and move it into an oven to dry at 80℃ to obtain a carbon-based composite catalyst, recorded as SCBC.

[0055] Comparative Example 3

[0056] Preparation of carbon-based composite catalysts:

[0057] Take 1g of biochar and disperse it in 100mL of ultrapure water. Then add 0.01mol of ferrous nitrate and stir for 2h. Then add a mixed solution of 0.4mol / L of sodium hydroxide and 0.4mol / L of sodium bicarbonate dropwise, adjust the pH value to 10, stir for 1h, put it in a 70℃ oven for aging for 24h, then filter it and move it into an oven to dry at 80℃ to obtain a carbon-based composite catalyst, recorded as SFBC.

[0058] The FTIR comparison diagram of the biochar (BC) used in the present invention, the SFCBC prepared in Example 1 and the FCBC prepared in Comparative Example 1 is shown in FIG. Figure 2 .

[0059] from Figure 2 It can be seen that the stretching vibration of the -OH groups adsorbed on the surface of all samples is at 3435 cm -1 There is a broad peak at 1580cm -1 The absorption peaks centered at 1421, 1304, 657, and 594 cm-1 are the stretching vibrations of interlayer water molecules (HOH) or C=C / C=O bonds in FeCo-LDH, while the absorption peaks at 1421, 1304, 657, and 594 cm-1 are the stretching vibrations of interlayer water molecules (HOH) or C=C / C=O bonds in FeCo-LDH. -1 The absorption peak is NO in FeCo-LDH 3 - , CO 3 2- , metal-O (MO) bonds, and metal-OH (M-OH) bonds. Compared with FCBC, the characteristic peaks of MO and M-OH bonds in SFCBC shifted slightly, indicating that sodium citrate modification enhanced the interaction between BC and FeCo-LDH.

[0060] Raman spectroscopy can be used to verify the presence of non-sp 2 Defects induced by hybrid carbon. The Raman comparison of the biochar (BC) used in the present invention, the SFCBC prepared in Example 1, and the FCBC prepared in Comparative Example 1 is shown in Figure 3 .

[0061] from Figure 3 It can be seen that BC, SFCBC and FCBC have the peaks at 1348 and 1595 cm -1 Two strong peaks were observed nearby, corresponding to the D band and G band of graphitized carbon. The intensity ratio of D band to G band (ID / IG) of SFCBC (0.89) is higher than that of FCBC (0.83) and BC (0.78), indicating that the introduction of sodium citrate will produce more defect sites.

[0062] Example 2

[0063] The carbon-based composite catalysts prepared above are used to activate potassium persulfate to degrade imidacloprid in water:

[0064] Experimental group: 0.010 g of SFCBC was added to 50 mL of imidacloprid solution (initial concentration was 5 mg / L, initial pH was 7), and then 0.012 g of potassium persulfate was added to the system to carry out catalytic degradation reaction for 15 minutes to complete the degradation of imidacloprid in the water.

[0065] Control group 1: Compared with the experimental group, the only difference was that SFCBC was omitted.

[0066] Control group 2: Compared with the experimental group, the only difference is that PMS is omitted.

[0067] Control group 3: Compared with the experimental group, the only difference was that SFCBC was replaced with FCBC of equal quality and PMS was omitted.

[0068] Control group 4: Compared with the experimental group, the only difference is that the SFCBC was replaced with FCBC of equal quality.

[0069] Control group 5: Compared with the experimental group, the only difference was that the SFCBC was replaced with SCBC of equal quality and PMS was omitted.

[0070] Control group 6: Compared with the experimental group, the only difference was that the SFCBC was replaced with SCBC of equal quality.

[0071] Control group 7: Compared with the experimental group, the only difference was that SFCBC was replaced with SFBC of equal mass and PMS was omitted.

[0072] Control group 8: Compared with the experimental group, the only difference is that the SFCBC was replaced with SFBC of equal quality.

[0073] After the catalytic degradation reaction was completed, the supernatant was aspirated with a syringe, passed through a 0.45 μm filter membrane, and the concentration of imidacloprid was determined at a wavelength of 270 nm using a high performance liquid chromatograph, and the removal rate of imidacloprid was calculated. The results are shown in Table 1.

[0074] Table 1 Removal rate of imidacloprid by different catalytic systems

[0075] Group Catalytic system Removal rate Experimental Group SFCBC+PMS 95.6% Control group 1 PMS 7.6% Control group 2 SFCBC 15.4% Control group 3 FCBC 12.7% Control group 4 FCBC+PMS 70.4% Control group 5 SCBC 10.8% Control group 6 SCBC+PMS 66.3% Control group 7 SFBC 9.1% Control group 8 SFBC+PMS 54.8%

[0076] As shown in Table 1, the SFCBC prepared by the present invention can efficiently activate peroxymonosulfate, significantly improve the degradation effect of imidacloprid, and the removal rate of imidacloprid can reach 95.6%. Compared with the case without sodium citrate modification, the present invention can improve the catalytic effect of the carbon-based composite catalyst from 70.4% to 95.6% by sodium citrate modification. In addition, compared with Fe or Co single metal modified biochar materials, the iron-cobalt double metal hydroxide modification strategy adopted by the present invention has a better modification effect on biochar.

[0077] After the catalytic reaction was completed, the precipitation of Fe and Co bimetallics in the experimental group was measured. After measurement, the precipitation concentration of iron in the reaction solution was only 0.031ppm, and the precipitation concentration of cobalt was 0.15ppm, which shows that the iron-cobalt bimetallics in the SFCBC of the present invention are not easy to fall off and precipitate, showing very excellent structural stability and can stably exert excellent catalytic performance.

[0078] Example 3

[0079] The SFCBC prepared in Example 1 was used in different amounts to activate potassium persulfate to degrade imidacloprid in water:

[0080] 0.010g, 0.015g, 0.020g and 0.025g of SFCBC were respectively added to 50mL of imidacloprid solution (initial concentration was 5mg / L, initial pH was 7), and then 0.026g of potassium persulfate was added to each system to carry out catalytic degradation reaction for 15min to complete the degradation of imidacloprid in the water.

[0081] During the catalytic degradation process, the supernatant was drawn with a syringe, filtered through a 0.45 μm filter membrane, and the concentration of imidacloprid was measured at a wavelength of 270 nm using a high performance liquid chromatograph, and the removal rate of imidacloprid was calculated. Figure 4 .from Figure 4 It can be seen that with the increase of catalyst dosage, the degradation efficiency of imidacloprid increased from 80.5% to 95.6%, which shows that the sodium citrate modified carbon-based composite catalyst can successfully activate potassium persulfate and achieve efficient degradation of imidacloprid. At the same time, when the catalyst dosage continues to increase from 0.3g / L, the improvement effect on IMI degradation is not obvious. Therefore, when the catalyst dosage is 0.3g / L, efficient treatment of imidacloprid can be achieved under lower cost conditions.

[0082] Example 4

[0083] The SFCBC prepared in Example 1 was used to activate different amounts of potassium persulfate to degrade imidacloprid in water:

[0084] Four portions of 0.015 g SFCBC were added to four 50 mL imidacloprid solutions (initial concentration was 5 mg / L, initial pH was 7), and then 0.006 g, 0.012 g, 0.018 g and 0.024 g of potassium persulfate were added to each system, respectively, and the catalytic degradation reaction was carried out for 15 minutes to complete the degradation of imidacloprid in the water.

[0085] During the catalytic degradation process, the supernatant was drawn with a syringe, filtered through a 0.45 μm filter membrane, and the concentration of imidacloprid was measured at a wavelength of 270 nm using a high performance liquid chromatograph, and the removal rate of imidacloprid was calculated. Figure 5 .from Figure 5 It can be seen that when the dosage of potassium persulfate increases from 0.12 g / L to 0.24 g / L, the removal rate of imidacloprid also increases from 85.9% to 95.6% within 15 minutes, and further increasing the concentration of potassium persulfate does not help the degradation of imidacloprid. Therefore, when the addition amount of potassium persulfate is 0.24 g / L, potassium persulfate can be efficiently activated with less catalyst, and efficient treatment of imidacloprid can be achieved.

[0086] Example 5

[0087] The SFCBC prepared in Example 1 was used to activate potassium persulfate to degrade imidacloprid in water bodies with different pH values:

[0088] Five portions of 0.015 g SFCBC were added to 50 mL of imidacloprid solution (initial concentration was 5 mg / L, and initial pH values ​​were 4, 6, 7, 8 and 10, respectively), and then 0.026 g of potassium persulfate was added to each system to carry out catalytic degradation reaction for 15 minutes to complete the degradation of imidacloprid in the water.

[0089] During the catalytic degradation process, the supernatant was drawn with a syringe, filtered through a 0.45 μm filter membrane, and the concentration of imidacloprid was measured at a wavelength of 270 nm using a high performance liquid chromatograph, and the removal rate of imidacloprid was calculated. Figure 6 .Depend on Figure 6 It can be seen that when the initial pH value of the imidacloprid solution is 4, 6, 7, 8 and 10, the removal rates of imidacloprid within 15 min are 96.4%, 93.3%, 95.6%, 92.7% and 90.9%, respectively.

[0090] Example 6

[0091] The SFCBC prepared in Example 1 was used to activate potassium persulfate to degrade imidacloprid in different water bodies:

[0092] Three portions of 0.015 g SFCBC were added to three 50 mL imidacloprid solutions (initial concentration was 5 mg / L, initial pH was 7, and the solvents were ultrapure water, tap water, and lake water, respectively). Then, 0.026 g potassium persulfate was added to each system to carry out catalytic degradation reaction for 15 minutes to complete the degradation of imidacloprid in the water.

[0093] After the catalytic degradation reaction was completed, the supernatant was aspirated with a syringe, passed through a 0.45 μm filter membrane, and the concentration of imidacloprid was determined at a wavelength of 270 nm using a high performance liquid chromatograph, and the removal rate of imidacloprid was calculated. The results are shown in Table 2.

[0094] Table 2 Removal rate of imidacloprid by the same catalytic system under different water conditions

[0095] Solvents Reaction time (min) Removal rate Ultrapure water 15 95.6% Tap water 15 94.9% Lake 15 83.8%

[0096] As can be seen from Table 2, the SFCBC prepared by the present invention has a rapid and efficient catalytic degradation effect on imidacloprid both under laboratory conditions and in actual water bodies, showing very excellent adaptability.

[0097] Example 7

[0098] The SFCBC prepared in Example 1 was used to activate potassium persulfate to treat different neonicotinoid insecticides in water:

[0099] Five portions of 0.015 g SFCBC were added to 50 mL of imidacloprid, thiamethoxam, clothianidin, dinotefuran and nitenpyram solutions (with initial concentrations of 5 mg / L and initial pH values ​​of 7, respectively), and then 0.026 g of potassium persulfate was added to each system to carry out catalytic degradation reaction for 15 minutes to complete the degradation of imidacloprid in the water.

[0100] During the catalytic degradation process, the supernatant was drawn with a syringe and filtered through a 0.45 μm filter membrane. The concentrations of imidacloprid, thiamethoxam, clothianidin, dinotefuran and nitenpyram were measured at wavelengths of 270 nm, 260 nm, 254 nm, 254 nm and 270 nm using a high performance liquid chromatograph, and the removal rates of imidacloprid, thiamethoxam, clothianidin, dinotefuran and nitenpyram were calculated. The degradation rates of different neonicotinoid insecticides in water by SFCBC activated potassium persulfate in Example 7 are shown in Table 1. Figure 7 .Depend on Figure 7 It can be seen that the SFCBC prepared by the present invention has a rapid and efficient catalytic degradation effect on a variety of neonicotinoid insecticides, showing very excellent application value.

[0101] Example 8

[0102] The SFCBC prepared in Example 1 was used to activate potassium persulfate to degrade imidacloprid in different water bodies:

[0103] Three portions of 0.015 g SFCBC were added to three 50 mL imidacloprid solutions (initial concentration was 5 mg / L, initial pH was 7), and then 0.026 g potassium persulfate was added to each system to carry out catalytic degradation reaction for 15 minutes to complete the degradation of imidacloprid in the water.

[0104] After the catalytic degradation reaction was completed, the supernatant was drawn with a syringe, filtered through a 0.45 μm filter membrane, and the concentration of imidacloprid was determined at a wavelength of 270 nm using a high performance liquid chromatograph, and the removal rate of imidacloprid was calculated. The catalyst used in the previous reaction was recovered for the next degradation experiment, and a total of 4 cycles were performed. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that the SFCBC catalyst prepared by the present invention can still maintain good catalytic activity during multiple cycles of use, showing its excellent structural stability and regeneration ability.

[0105] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a defect-rich sodium citrate-modified carbon-based composite catalyst, characterized in that: The following steps are involved: Biochar, soluble ferrous salt, soluble cobalt salt and sodium citrate are dispersed together in water, and then a mixed solution of sodium hydroxide and sodium bicarbonate is added to adjust the pH value of the reaction system to 10-10.

5. After the reaction raw materials are fully mixed, an aging reaction is carried out to obtain a defect-rich sodium citrate modified carbon-based composite catalyst.

2. The method for preparing the defect-rich sodium citrate modified carbon-based composite catalyst according to claim 1, characterized in that: In the reaction system, the concentration of the biochar is 10-50 g / L, Fe 2+ The concentration of Co is 0.05mol / L~0.15mol / L, 2+ The concentration of the sodium hydroxide is 0.05mol / L-0.15mol / L, the concentration of the sodium citrate is 0.001-0.01mol / L, the concentration of the sodium hydroxide in the mixed solution of sodium hydroxide and sodium bicarbonate is 0.2-0.4mol / L, and the concentration of the sodium bicarbonate is 0.2-0.4mol / L.

3. The method for preparing the defect-rich sodium citrate modified carbon-based composite catalyst according to claim 1, characterized in that: The temperature of the aging reaction is 60-80° C. and the time is 18-30 hours.

4. The method for preparing the defect-rich sodium citrate modified carbon-based composite catalyst according to claim 1, characterized in that: The aging reaction further includes filtering and drying steps.

5. The method for preparing the defect-rich sodium citrate modified carbon-based composite catalyst according to claim 4, characterized in that: The drying temperature is 80-100°C.

6. A defect-rich sodium citrate-modified carbon-based composite catalyst prepared according to the method for preparing a defect-rich sodium citrate-modified carbon-based composite catalyst according to any one of claims 1 to 5.

7. Use of the sodium citrate modified carbon-based composite catalyst according to claim 6 in activating persulfate.

8. Use of the sodium citrate modified carbon-based composite catalyst according to claim 6 in degrading neonicotinoid pesticides in water.

9. The use according to claim 8, characterized in that: The degradation step comprises: adding the sodium citrate-modified carbon-based composite catalyst and persulfate to water containing the neonicotinoid insecticide, and completing the degradation treatment of the neonicotinoid insecticide in the water after the reaction.

10. The use according to claim 9, characterized in that: The addition amount of the sodium citrate modified carbon-based composite catalyst is 0.2-0.5 g / L; the persulfate is one or a mixture of peroxymonosulfate and peroxydisulfate; the addition amount of the persulfate is 0.12-0.48 g / L; the reaction time is 10-30 min; and the concentration of the neonicotinoid insecticide is 1-20 mg / L.